Investigation of Mig Welding to Corrosion Behavior of Heat Treated Carbon Steel - Shing Shian, Ng; Nur Azhani, Abd Razak (2013)
This paper presents corrosion behaviour of heat treated and welded low carbon steel at different welding voltage and filler materials. Welding process was conducted on butt joint specimens using Metal Inert Gas (MIG) technique at welding voltage range of 19 to 21 V with 1 V interval and filler materials used were ER 308L and ER 70S-6 with 1.2 mm diameter. Heat treatment of full annealing was done to the welded low carbon steel and corrosion behaviour was tested using synthetic seawater environment with 3.5 wt% NaCl. Microstructure changes were observed using Scanning Electron Microscope (SEM). Results showed that, corrosion rate decreased when welding voltage increased as it directly affected welding heat input. The welding heat input was found to have a significant effect to corrosion rate as it changed the ferrite content on the microstructure of the specimens. The decreased in corrosion rate was also found when full annealing process was done to the specimens and the used of ER 70S-6 filler material. From metallographic study, iron oxides and pitting was found on the surface of the exposed area after the corrosion test.